Influence of crystalline Zn-Ag nanoalloy electrodeposits on their anti-corrosion and hardness performance in engineering applications - Gnanamuthu R.M.; Saravanan G.; Kandasamy M.; Jesudoss S.K.; Ponraj G.B.; Rajkumar P.; Sivakumar M.; Jothivenkatachalam K.; Srinivasan D. (Springer Science and Business Media Deutschland GmbH, 2025)
The main goal of the current work is to develop external excellence, hardness, and anti-corrosion quality materials for engineering and metal finishing applications. To design and prepare a binary type of Zn-Ag nanoparticles as an alloy substantial over on mild steel (MS) engineering substrate using direct current (DC) electrochemical deposition. In this regard, silver nanoparticles are evenly distributed throughout the pure zinc with high-quality surface. Some different bath compositions, experimental settings, and parameters are used to optimize Zn-Ag nanoalloy coatings. The prepared specimen is examined using energy-dispersive X-ray spectroscopy (EDS), field-emission scanning electron microscope (FE-SEM), and X-ray diffraction (XRD). The XRD data for the AgZn3 phase demonstrate well-crystalline properties with reference pattern JCPDS 00?025-1325. Investigations are conducted into electrochemical research, including the Tafel corrosion test and electrochemical impedance spectroscopy (EIS). The results showed AgZn3 and Zn lower values of Icorr (1 ? 10?5 A cm?2) compared to the Zn (1 ? 10?3) sample, a greater corrosion potential (Ecorr) of ? 0.9V and ? 0.6V, respectively, when deposited on MS substrate. For technical and automotive applications, the produced AgZn3 on MS therefore shows the optimum corrosion resistance and hardness surface with compact microstructure. ? The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature 2024.